The Role of Re-laparoscopy in the Management of Complications Following Laparoscopic Rectal Cancer Surgery: A Retrospective Case Series - Anahita Attaran; Fatemeh Shahabi; Ala Orafaie; Majid Ansari; Reza Rezaei; Abbas Abdollahi (Iranian Journal of Colorectal Research, 2023)
Introduction: The benefits of laparoscopy versus open surgery for patients with rectal cancer have been well established. This study evaluates the role of re-laparoscopy in patients who develop complications following laparoscopic rectal cancer surgery.Methods: This is a retrospective case series of 22 (5.9%) re-laparoscopy cases of the 373 rectal cancer patients with rectal cancer who underwent laparoscopic primary surgery at Omid, Ghaem, and Razavi hospitals in Mashhad, Iran, between July 2011 and December 2020.Results: Twenty-two (5.9%) eligible patients with a mean±SD age of 50.9±10.4 years were included in the study, of which 15 (68.2%) were men and 7 (31.6%) were women. After 22 primary laparoscopic surgeries, anastomosis-fail/peritonitis was the most common complication requiring re-laparoscopy (n=9, 40.9%). Other complications included obstruction (n=8, 36.4%), bleeding (n=3, 13.6%), and intestinal injury (n=2, 9.1%). The complications of all patients (n=22) who underwent re-laparoscopy were successfully managed by re-laparoscopy.Conclusion: In the case of available facilities and the presence of an experienced surgeon in the medical center, re-laparoscopy for managing complications following laparoscopic rectal cancer surgery appears to be safe and effective in selected patients.